Menelaah Dinamika Komunikasi Politik dalam Masyarakat Modern - Anitha Nurchalisah Thaha; Qudratullah Qudratullah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Political communication is a crucial element in shaping public opinion, especially in the modern era influenced by the rapid development of information technology. This study aims to analyze the dynamics of political communication in contemporary society by highlighting the role of social media, political figures, and public participation in political discourse. The research employs a qualitative approach through literature review and discourse analysis of political communication phenomena in Indonesia. The findings reveal that political communication in the modern era is two-way, interactive, and heavily influenced by the fast-paced flow of digital information. This study is expected to contribute to enhancing political literacy and deepening public understanding of contemporary political dynamics.